The children's blizzard : a novel - Benjamin, Melanie, 1962- (Delacorte Press, 2021)
Draws on oral histories of the Great Plains blizzard of 1888 to depict the experiences of two teachers, a servant, and a reporter who risk everything to protect the children of immigrant homesteaders.